Dismetría y características posturales en personas con amputación de extremidad inferior y análisis de su alineación protésica - López Bravo, Julia; Alemón, B.; Huegel, J. C. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Lower limb amputees (LLAm) with prosthetic limbs get through alignment and leveling processes to assure the correct function of their device. However, errors in this process may led to lower limb asymmetry (LLA). Depending on the magnitude of the LLA there is a greater risk of presenting postural asymmetry, gait disturbances, low back pain, and structural deformities. Therefore, the main objective of this article is to determine LLA and alignment and postural features of people with lower limb (LL) amputation using the software Kinovea. Nowadays there is not much literature about the postural and asymmetry analysis of LLAm. The method followed to calculate the asymmetry was to first do the software calibration with a chosen reference segment, then each leg segment was measured using Kinovea to obtain the absolute difference between them. The angles of knee flexion and alignment were also analyzed with the help of marks previously placed in the subjects’ points of interest. Among the 16 subjects, 8 presented an asymmetry level I, 3 a level II and 5 a level III, in the lateral position. The longest LL of 11 of the 13 unilateral amputees presented the smallest knee flexion angle. The subjects’ knee stability was classified as stable for 7 of them, as unstable for 9 and only 1 subject as extremely stable. The main application of the results obtained would be to use the information to create a database that can be used for future research and as feedback for prosthetists and orthotists.